THE OBJECTIVE OF ISLAMIC EDUCATION ACCORDING TO CONTEMPORARY EDUCATION FIGURES BASED ON THINKING OF THE HUMAN ESSENCE - Dartim Dartim (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2021)
Education is a process of humanizing humans. Humans who are worthy to be role models on earth, and humans who can heed the good life order. Either according to religious guidelines or according to other norms. Efforts to formulate concepts of education are part of an operational framework so that the educational goals of each concept can be realized. Therefore, this study was conducted using the approach of contemporary thinkers through the thoughts of Mohamad Iqbal, Al-Attas, Al-Faruqi, and Hossein Nasr. The study was conducted with a qualitative method approach because the data used were sourced from literacy data